Litchi‐derived platinum group metal‐free electrocatalysts for oxygen reduction reaction and hydrogen evolution reaction in alkaline media - Seyed Ariana Mirshokraee; Mohsin Muhyuddin; Roberto Lorenzi; Giorgio Tseberlidis; Carmelo Lo Vecchio; Vincenzo Baglio; Enrico Berretti; Alessandro Lavacchi; Carlo Santoro (SusMat, 2023)
Abstract Within the framework of the circular economy, the waste litchi's skins were upgraded and transformed into electrocatalysts for oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). The waste litchi's skins were pyrolyzed, activated, and then used as carbon support for fabricating metal–nitrogen–carbons (M–N–Cs) which belong to a promising class of platinum group metal‐free electrocatalysts. The activated char was functionalized with transition metal (Fe, Ni, and Co)‐ phthalocyanine (Pc) in monometallic and bimetallic fashion by subjecting it to a thermal treatment at 600 and 900°C. The samples functionalized at 900°C showed higher performance for HER due to the formation of metal nanoparticles, whereas the samples functionalized at 600°C showed higher performance for ORR. Particularly, sample Ni–Co 900 had an overpotential of −0.38 V for HER, while the sample Fe 600 was the most active electrocatalyst for ORR by demonstrating the onset potential of ∼0.9 V (a half‐wave potential of ∼0.81 V) with the least production of unwanted peroxide anion.